Pengaruh Aktivis Mahasiswa Dalam Perubahan Sosial Politik Di Era Digital 5.0 - Syahputri, Icca Bela; Katimin, Katimin (Jayapangus Press, 2024)
The study explores how student activists at the Islamic State University of North Sumatra (UINSU) influence the socio-political dynamics of the digital era 5.0. This era is marked by technological advances that integrate the physical, digital, and biological worlds, thus providing a new platform for student activism. Student activists not only act as agents of change through social and political activities, but they also use digital technology to expand their influence. The research uses a survey method with structured questionnaires distributed to UINSU student activists, as well as a qualitative approach to gaining an in-depth understanding of their views, attitudes, and experiences of socio-political change. Research findings indicate that student activists effectively use social media and digital technology for campaigns and mobilization. Through social media and internet platforms, activists can quickly mobilize people and draw attention to key topics such as gender equality, climate change, and human rights on a global scale. In the digital age of 5.0, student activists can also more successfully challenge existing forces by using digital tactics, including online campaigns, digital petitions, and online boycott movements, in addition to conducting physical demonstrations in public spaces. They not only use technology as a tool of struggle, but also as a new space for building critical awareness and solidarity. However, the research also finds challenges faced by student activists, such as the spread of disinformation and hoaxes, digital gaps, and technology access. Nonetheless, student activists continue to adapt quickly and innovate to overcome these barriers. The study provides significant insights into the role of digital technology in student activism and its implications for healthy political participation in the digital age 5.0, as well as solutions to strengthen the integrity of democracy at the local level.